INTERNALISASI NILAI AKHLAKUL KARIMAH DALAM MEMBENTUK KARAKTER ANAK - Ali Muhsin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
The Muhammadiyah Dlanggu Orphanage Mojokerto is a place to educate children who are disadvantaged in teaching from their parents, because of problems from 40 children, some who disobey, who like to disobey the rules, the Muhammadiyah Orphanage Mojokerto has programs for character briefing child. This study aims to determine the implications of the cultivation of moral values to foster children. The research design used is qualitative, with data collection methods namely observation, interviews, and documentation. Data analysis techniques with Flow Model which includes data reduction, data display, conclusion. The conclusions of this study are: the process of planting the character values of an orphanage by instilling the value of akhlakhul karimah through a religious approach, cultural values, environment, self potential, and daily life. The implication is that foster children get new knowledge learning that can change their daily lives for the better. The inhibiting factor is that the origin of the environment is not good because of the number of naughty children and lack of cultivation of moral values since childhood from their parents.